Penerapan Teknik Quilting dalam Pemanfaatan Kain Perca untuk Pengembangan Desain Fashion Outerwear - Yoga Evan Dwi Kristantyo; Koniherawati; Winta Adhitia Guspara (Meraki: Journal of Creative Industries, 2025)
The fashion industry is a rapidly growing sector that also contributes to increasing textile waste, one of which is fabric scraps. Often perceived as worthless, fabric scraps have great potential to be transformed into functional and aesthetic products. This study aims to explore the utilization of fabric scraps through quilting techniques in developing sustainable outerwear designs. The research uses a qualitative exploratory method with the M.A.C.A.K approach (Material, Tools, Method, Attributes, and Context). The results show that fabric scraps can be processed into textured and layered materials suitable for outerwear design. The resulting products are jackets and vests developed under the concepts of nature- inspired fashion and sheer layering, emphasizing aesthetics, functionality, and sustainability.